2016
DOI: 10.7717/peerj.2636
|View full text |Cite
|
Sign up to set email alerts
|

Elevational pattern of bird species richness and its causes along a central Himalaya gradient, China

Abstract: This study examines the relative importance of six variables: area, the mid-domain effect, temperature, precipitation, productivity, and habitat heterogeneity on elevational patterns of species richness for breeding birds along a central Himalaya gradient in the Gyirong Valley, the longest of five canyons in the Mount Qomolangma National Nature Reserve. We conducted field surveys in each of twelve elevational bands of 300 m between 1,800 and 5,400 m asl four times throughout the entire wet season. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
58
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 79 publications
(128 reference statements)
15
58
0
3
Order By: Relevance
“…Because there are flat, less vegetation diversity and settlements at the plateau of the areas in which any sightings were not recorded. But based on DEM analysis, the species showed a marked preference at mid elevation level, such as Block A, Block B and Block C. This finding agrees with Acharya et al (2011) and Pan et al (2016) that bird richness in the eastern and central Himalaya region was higher at middle elevation gradients.…”
Section: Measuring Human Disturbances Within Line Transectssupporting
confidence: 82%
“…Because there are flat, less vegetation diversity and settlements at the plateau of the areas in which any sightings were not recorded. But based on DEM analysis, the species showed a marked preference at mid elevation level, such as Block A, Block B and Block C. This finding agrees with Acharya et al (2011) and Pan et al (2016) that bird richness in the eastern and central Himalaya region was higher at middle elevation gradients.…”
Section: Measuring Human Disturbances Within Line Transectssupporting
confidence: 82%
“…In our study, the effect of area was variable (Table 3). This is the case with our results in the eastern slope subregion, which lack significant relationship, McCain (2007) and Pan et al (2016) found that the area is not identified as a main driving force and is not a crucial factor in determining species richness. In our case, the main factor is that the diversity in a certain elevational zone is strongly influenced by very local "hotspots," with many species restricted to places with riparian forest or cloud forest.…”
Section: The Role Of Climatic Factorssupporting
confidence: 68%
“…while it exhibited a hump-shaped pattern on the western slope and wet side(Figure 3). However, precipitation, as measured for the different elevational zones, is not a crucial predictor for elevational diversity(Pan et al, 2016). The relationship is positive in the wet side and negative in the dry side.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Several drivers have been proposed to explain these patterns, including the current climate, space, evolutionary history, and biotic processes (reviewed in McCain, ). However, spatial (e.g., area, mid‐domain effect (MDE)) (Colwell, Rahbek, & Gotelli, ; Rahbek, ) and environmental drivers (e.g., climatic variables, productivity, and habitat heterogeneity) are cited most frequently (e.g., Nogués‐Bravo, Araújo, Romdal, & Rahbek, ; Sanders & Rahbek, ; Wu et al, ; Pan et al, ; Hu et al, ; Elsen, Tingley, Kalyanaraman, Ramesh, & Wilcove, ). For example, McCain () conducted a meta‐analysis of global elevational patterns of birds, and found both water and temperature variables were important drivers of elevational diversity gradients.…”
Section: Introductionmentioning
confidence: 99%